ANALISIS TENTANG DAMPAK APLIKASI TIK TOK PADA SISWA SDN 65 DESA SUKA RAMI KECAMATAN KEDURANG ILIR KABUPATEN BENGKULU SELATAN - Yunita, Herma; Wijayanti, Ayu (JURNAL ILMIAH IDEA, 2024)
This study aims to describe the impact of using the TikTok application on students of SDN 65 Suka Rami Village, Kedurang Ilir District, South Bengkulu Regency. To achieve the research objectives, the researcher used a qualitative research method, with the concept of the impact of using the TikTok application on dating behavior using a case study approach. Research informants were determined through purposive sampling techniques, which means that researchers first determine the criteria for informants in order to filter informants that are in accordance with research needs. Research data were collected through data collection techniques, namely observation, interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study were then analyzed using the behavioral theory proposed by B.F. Skinner. This theory focuses on human behavior through the results of stimuli in the surrounding environment and individual responses to these stimuli. The results of the study showed that the use of the TikTok application by students of SDN 65 Suka Rami Village, Kedurang Ilir District, South Bengkulu Regency had a positive impact because it made them tend to be more active and creative, their self-confidence levels became higher, and they had skills in editing videos or photos. But there are also negative impacts from using the TikTok application, namely 1) often seeing negative content, 2) Waste, 3) and changes in ethics.